2023
DOI: 10.3390/ijms241814322
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between the Host Genome, Epigenome, and the Gut–Skin Axis Microbiome in Atopic Dermatitis

Rodrigo Pessôa,
Patricia Bianca Clissa,
Sabri Saeed Sanabani

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease that occurs in genetically predisposed individuals. It involves complex interactions among the host immune system, environmental factors (such as skin barrier dysfunction), and microbial dysbiosis. Genome-wide association studies (GWAS) have identified AD risk alleles; however, the associated environmental factors remain largely unknown. Recent evidence suggests that altered microbiota composition (dysbiosis) in the skin and gut may contribute to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 153 publications
(171 reference statements)
0
6
0
Order By: Relevance
“…On the human skin, various bacteria, including C. acnes and S. aureus , produce short-chain fatty acids such as lactic acid [32]. Moreover, S. aureus and C. acnes produce lipases that produce free fatty acids from sebum [27], which can decrease the pH of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…On the human skin, various bacteria, including C. acnes and S. aureus , produce short-chain fatty acids such as lactic acid [32]. Moreover, S. aureus and C. acnes produce lipases that produce free fatty acids from sebum [27], which can decrease the pH of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that dysbiosis of the gut microbiota, characterized by a reduction in SCFAs-producing bacteria, plays a pivotal role in the development of AD (81). For instance, Clostridium, Prevotella, Clostridia, Bifidobacteraceae, Bifidobacterium, Bacteroidetes, Christensenellaceae_R7_group, and other bacterial species have been found to be decreased (82)(83)(84)(85). Additionally, the "gut-skin" axis has emerged as a novel therapeutic target for the prevention and management of AD.…”
Section: Discussionmentioning
confidence: 99%
“…It is a well-known fact that patients with AD present differences in terms of gut microbiota in comparison to healthy individuals, and this can also be a subject of study and an explanation for the higher prevalence of certain diseases in AD patients or the other way around [86]. According to the review conducted by Pessoa et al, patients with AD have a higher prevalence of Clostridium difficile and Staphylococcus aureus in comparison to healthy individuals, contrary to reduced colonization of Bifidobacteria and Bacteroides when compared to healthy controls [86]. Additionally, it is worth mentioning that recent research on the role of dysbiosis in the gut microbiota in the pathogenesis and course of AD has made progress.…”
Section: Discussionmentioning
confidence: 99%